Digitalizarea Dicționarului general al literaturii române. (I) Metode de abordare și direcții de cercetare - Laurențiu Hanganu (Revista de Istorie și Teorie Literară, 2020)
The paper presents the results of the process of digitization of the General Dictionary of Romanian Literature and the new possibilities brought about by the information technology for the humanities research as highlighted by the academic project entitled “Preservation and Capitalization of Romanian Literary Patrimony by Means of Intelligent Digital Solutions for Data Mining and Systematization” (INTELLIT).